MANAGEMENT OF HELLP SYNDROME BEFORE DELIVERY: A COMPREHENSIVE SYSTEMATIC REVIEW - Christian, Roy; Pieter Hetharia, Frenki; Bangkit Sumardi, Franky; Dwi Rahayu, Inggit (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: HELLP syndrome, a rare and serious complication during pregnancy, poses significant risks to both mother and fetus. Early management of HELLP syndrome before delivery may improve the outcomes for patients. This study aims to systematically review literatures on HELLP syndrome management before delivery in the last 10 years. Methods: This systematic review complied with the PRISMA 2020 standards and focused on full-text English literature published between 2014 and 2024. Articles such as editorials and review papers from the same journal, as well as submissions lacking a DOI, were excluded from consideration. Literature was sourced from online platforms like PubMed and SagePub. Result: We found 1629 articles on PubMed and 560 articles on SagePub. Restricting our search to the past decade (2014-2024), PubMed presented 507 articles, whereas SagePub presented 288 articles. From these, we selected 5 papers meeting our criteria, with 3 from PubMed and 2 from SagePub. Conclusion: The main treatment approach for HELLP syndrome involves stabilizing the mother and ensuring timely delivery. Various strategies, including the use of corticosteroids and glucocorticoids, have been explored to reduce the associated morbidity and mortality.